2021
DOI: 10.21203/rs.3.rs-148212/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementing a New Dose-response Model for Estimating Infection Probability of Campylobacter Jejuni based on the Key Events Dose-response Framework

Abstract: Understanding the dose-response relationship between ingested pathogenic bacteria and infection probability is a key factor for appropriate risk assessment of foodborne pathogens. The objectives of this study were to develop and validate a novel mechanistic dose-response model for Campylobacter jejuni and simulate the underlying mechanism of foodborne illness during digestion. Bacterial behavior in the human gastrointestinal environment, including gastric reductions, transition to intestines, and invasion to i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There already have been some examples for application of a simple growth prediction in intestines for mechanistic dose-response model (Rahman et al, 2016(Rahman et al, , 2018, although they used simple monocultured behaviour for L. monocytogenes doseresponse model. Recently, reported that the cell-invasion rate of C. jejuni into human intestinal cells depends on the pathogen concentration around intestinal cells, and the prediction of cell-invading behaviour has the potential to estimate dose-response relationship Abe, Takeoka, 2021). Therefore, an accurate estimation of the pathogen concentration in human intestinal tracts will be necessary for estimating the dose-response model for pathogens such as C. jejuni, L. monocytogenes and Salmonella spp., which invade body tissues and cause adverse health effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There already have been some examples for application of a simple growth prediction in intestines for mechanistic dose-response model (Rahman et al, 2016(Rahman et al, , 2018, although they used simple monocultured behaviour for L. monocytogenes doseresponse model. Recently, reported that the cell-invasion rate of C. jejuni into human intestinal cells depends on the pathogen concentration around intestinal cells, and the prediction of cell-invading behaviour has the potential to estimate dose-response relationship Abe, Takeoka, 2021). Therefore, an accurate estimation of the pathogen concentration in human intestinal tracts will be necessary for estimating the dose-response model for pathogens such as C. jejuni, L. monocytogenes and Salmonella spp., which invade body tissues and cause adverse health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Abe, Koyama, et al ( 2021 ) reported that the cell‐invasion rate of C . jejuni into human intestinal cells depends on the pathogen concentration around intestinal cells, and the prediction of cell‐invading behaviour has the potential to estimate dose–response relationship (Abe, Koyama, et al, 2021 ; Abe, Takeoka, 2021 ). Therefore, an accurate estimation of the pathogen concentration in human intestinal tracts will be necessary for estimating the dose–response model for pathogens such as C .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations